Rare Co-Occurrence of Visual Snow in a Female Carrier With RPGRORF15-Associated Retinal Disorder - Tuekprakhon, Aekkachai; Pawestri, Aulia Rahmi; Suvannaboon, Ragkit; Thongyou, Ketwarin; Trinavarat, Adisak; Atchaneeyasakul, La-Ongsri (Frontiers in Genetics, 2021)
X-linked retinitis pigmentosa (XLRP), a rare form of retinitis pigmentosa (RP), is predominantly caused by mutations in the retinitis pigmentosa GTPase regulator (RPGR) gene. Male patients often present with more severe phenotypes and early disease onset, while female carriers are usually asymptomatic or show stationary phenotypes. Herein, we reported the co-occurrence of progressive cone dystrophy and visual snow-like symptom in a female carrier of RPGR mutation. An 8-year-old female, daughter from a confirmed RP father with RPGR gene mutation, has been experiencing a visual snow-like symptom as long as she recalled. Ophthalmological examination showed the reduction of visual acuity and attenuation of photoreceptor functions since the age of 5 years. Mutation analysis revealed heterozygous pathogenic variant of the RPGR gene and X-inactivation analysis demonstrated a random X-inactivation pattern. The information on the variety of genotypic and phenotypic presentations in XLRP carriers is essential for further diagnosis, management, and monitoring of these cases. Follow up data in carriers could also aid in shaping the inheritance pattern of this condition.